Overview of ChatGPT Technology and its Potential in Improving Tourism Information Services - Muhammad Ade Kurnia Harahap; Abu Muna Almaududi Ausat; Andy Rachman; Yasir Riady; Hizbul Khootimah Azzaakiyyah (Politeknik Ganesha Medan, 2023)
Tourism is one of the important economic sectors for many countries, including Indonesia. Along with the development of technology and the internet, the way people seek information about tourism has also changed. This research aims to conduct a review of ChatGPT technology and its potential in improving tourism information services. The focus of this research is qualitative. Methods for gathering information included paying close attention and taking detailed notes, with subsequent analysis including data reduction, visualisation, and inference. The study arrived at the conclusion that the use of AI technology specifically ChatGPT has great potential in improving services and traveller experience in the tourism industry. ChatGPT can assist service providers in providing solutions and answering tourists' questions quickly and efficiently, as well as strengthening the position of the company or organisation amid increasingly fierce competition.